An Efficient Multistage Authentication System - Mishra, KV; Sanas, PJ; Sapkal, NA; Pansare, AP; Deogire, AD (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes a multilayer security system, which can be used at domestic, organization and industrial level as a strict safety and regulatory measure to prevent thefts and unauthorized access. Here, we incorporate the three best measures into one multilayer security which is a sequence of RFID, Biometric and Password module system. These modules are controlled through Arduino (UNO r3) microcontroller based board. If the RFID tag content, password and fingerprint image confirmation are matched, then only the user will be allowed to access to the organization. We propose a more efficient and reliable system that can provide multilevel security which would be difficult to breach and a system that would digitize that particular organization.